PENGARUH KEPEMIMPINAN, MOTIVASI, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA RITUAL KOPI DENPASAR, BALI - Thegi Mintara; Ni Made Dwi Puspitawati; Ni Luh Gede Putu Purnawati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
This research aims to test and analyze the influence of participative leadership, motivation and work discipline on employee performance. This research was conducted at Denpasar Coffee Ritual, Bali in East Denpasar District with a research sample of 37 respondents taken using saturated sampling techniques. All data obtained from the questionnaire distribution is suitable for use, then analyzed using multiple linear regression, hypothesis testing (t test and f test). The results of the research show that (1) Participative Leadership has a positive and significant effect on Employee Performance at the Denpasar Coffee Ritual, Bali, so that the better the Participative Leadership, the more Employee Performance at the Denpasar Coffee Ritual, Bali will increase (2) Motivation has a positive and significant effect on Performance Employees at the Denpasar Coffee Ritual, Bali so that the more motivation increases, the more employee performance at the Denpasar Coffee Ritual, Bali (3) Work Discipline has a positive and significant effect on Employee Performance at the Denpasar Coffee Ritual, Bali, so that the greater the Work Discipline, the greater the performance. Employees at Ritual Kopi Denpasar, Bali.